2005
DOI: 10.3844/ajessp.2005.270.277
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance of a Solar Heat Storage Accumulator Used For Greenhouses Conditioning

Abstract: Abstract:The use of solar energy for greenhouse heating has gained an increasing acceptance during the last years. Active solar systems applied to greenhouses can supply a significant part of the heating requirements. However, there are some problems related to the cost of the heat collection unit and the heat storage methods. In this context several techniques were born. The most famous of these techniques is the seasonal storage of thermal heat in soil. The objective of our work is to study a system of therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
7
0
2
Order By: Relevance
“…Потреби людства в споживанні енергії постійно збільшуються, відповідно збільшується видобуток при-родних ресурсів, що призводить до зростання їх цін [1,2]. Екологічний стан довкілля та постійне зростання цін на імпортовані енергоносії зумовлює пошук нових джерел енергії, упровадження енерозберігаючих тех-нологій, реконструкцію й удосконалення потужностей, що існують, в енергетичному, житлово-комунальному, промисловому секторах.…”
Section: вступunclassified
See 1 more Smart Citation
“…Потреби людства в споживанні енергії постійно збільшуються, відповідно збільшується видобуток при-родних ресурсів, що призводить до зростання їх цін [1,2]. Екологічний стан довкілля та постійне зростання цін на імпортовані енергоносії зумовлює пошук нових джерел енергії, упровадження енерозберігаючих тех-нологій, реконструкцію й удосконалення потужностей, що існують, в енергетичному, житлово-комунальному, промисловому секторах.…”
Section: вступunclassified
“…Microreactors offer several opportunities to optimize the reaction systems due to high specific interfacial area improving heat and mass transfer, the smaller working volumes, continuous mode of operation, efficient operation, low wastage of chemicals and intrinsic safety [1]. Potential advantages of microstructured reactors (MSR) allow successfully use them to complex processes for optimization and scale-up from the laboratory scope to production.…”
Section: Introductionmentioning
confidence: 99%
“…Одним з найбільш перспективних джерел тепла є Сонце, що зумовлено рядом факторів: сонячна енергетика доступна в кожній точці нашої Планети, яка відрізняється за густиною потоку сонячного випромінювання не більше, ніж в два рази; також вона є екологічно чистим та невичерпним джерелом теплоти без негативного впливу на навколишнє середовище [4]. Як відомо потенціальні можливості сонячної енергетики є надзвичайно великими.…”
Section: вступunclassified
“…Many researches around this subject were carried out in the world especially in this region. (Copaciu and Yousef, 1999;Hazami et al, 2005), In Romania, a study of atmospheric responses due to the 11 August total solar eclipse indicated that both of the global and UVB radiation dropped dramatically to a minimum around totality. There was a chance to study attenuation of such a radiation due to clouds.…”
Section: Introductionmentioning
confidence: 99%